'Legal Formalism' and Western legal thought*. (2nd January 2023) - Preuß, Karlson
ABSTRACT: According to long-established narratives, legal thinking in Germany, France and the U.S.A. was shaped by formalist legal cultures for the most part of the nineteenth century until the respective legal sciences embraced their social responsibility in the early twentieth century. Recently, legal historians have begun to question these narratives. In separate analyses, they have shown that the critics of 'Legal Formalism' exerted a lasting influence on historical research since the early twentieth century, thereby fostering a deeply charged understanding of nineteenth century jurisprudence. What went largely unnoticed, however, was the transnational dimension of this false narrative. Due to the transnational ties of the critics of 'Legal Formalism', a powerful misrepresentation of nineteenth century Western legal thought emerged that still influences contemporary global legal history. Dismantling the prejudices surrounding the Western jurisprudence of the nineteenth century causes crucial challenges for conceptualising nineteenth century Western legal thought.